Strategic Cost Management Techniques System in Management and Accounting Thought: An Application Guide - Sirwan kareem Issa; Mohammed Abdullaziz Mohsin (QALAAI ZANIST JOURNAL, 2020)
Strategic cost management techniques receive a lot of attention from economic units, especially industrial ones, especially after the financial crisis in the first decade of the current century. Increased interest in reducing costs that do not add value to the consumer in all parts of the value chain, hence strategic cost management techniques have become a field of research And the study by the accountant researchers, and for this purpose, research shows the integrative relationship between administrative and accounting thought in relation to the techniques of strategic cost management, so that this thought becomes a guide for proper application. The research focuses on presenting the concept and types of technologies in light of the main administrative functions such as formulating strategic planning and analyzing internal and external situations. It tries to present a theoretical framework to serve as a guide to success under the name of the strategic cost management techniques system. Based on this, the research problem lies in demonstrating that the appropriate selection process among strategic cost management techniques depends on the strategic vision of the economic units. The researchers relied on the scientific and analytical method to derive the results. Among the most important findings of the research is that strategic cost management techniques are a comprehensive system for managing costs that relate to the provision of goods and services in all parts of the value chain. It is closely related to the strategic vision of the economic units.